Influence of adhesive and thermal cycling on the bond strength of ceramic brackets to dental ceramic - Patricia de Fátima Fraga; Ana Paula Terossi de Godoi; Ana Rosa Costa; Lourenço Correr-Sobrinho; Mario Vedovello Filho; Heloisa Cristina Valdrighi (Universidade Estadual de Campinas, 2017)
Aim: This in vitro study investigated the effect of the application of an adhesive, silane and thermal cycling (TC) on the shear bond strength (SBS) of ceramic brackets to feldspathic ceramic. Methods: 16 cylinders of feldspathic ceramic were etched with hydrofluoric acid and divided into four groups (n=4): G1 - silane, without TC; G2 - silane, with TC; G3 - adhesive, without TC; G4 - adhesive, with TC. One layer of silane was applied on the surface of cylinders in G1 and G2 e one layer of photo-activated adhesive Single Bond Universal was used in G3 and G4. Ceramic brackets were bonded using Transbond XT. The SBS data were subjected to two-way ANOVA and Tukey's post hoc test (α=0.05). The Adhesive Remnant Index (ARI) was evaluated at 40× magnification. Results: Silane was more effective than adhesive on the SBS of the brackets to ceramic (p<0.05). TC decreased significantly the SBS values compared with the groups without TC (p<0.05). The ARI results showed predominance of score 0. Conclusions: Groups with silane showed higher SBS than groups with adhesive. TC influence significantly on the bond strength. Regarding ARI, score 0 predominated in all groups.